Antibiotic resistance evaluation and clinical analysis of acute appendicitis; report of 1431 consecutive worldwide patients: A cohort study. (February 2016) - Coccolini, Federico; D'Amico, Giuseppe; Sartelli, Massimo; Catena, Fausto; Montori, Giulia; Ceresoli, Marco; Manfredi, Roberto; Di Saverio, Salomone; Ansaloni, Luca
Abstract: Background: Acute appendicitis (AA) is one of the most common diseases affecting especially young but also older people. A systematic evaluation of bacteriology of AA has been frequently conducted in children but is not well known and discussed in adult population. Study design: The study has been obtained from two multicenter prospective observational studies (CIAO and CIAOW studies). The aim of the study is to analyze the intra-abdominal bacteriology in AA and its relation with clinical outcomes. Results: Patients included were 1431, 806 male (56.3%). The mean/median age was 38.9 (SD ± 18.4) and 35 (range 18–94). Clinical condition at the admission was sepsis in 623 patients (43.5%), severe sepsis and septic shock in 29 (2%) and 10 (0.7%). Peritonitis was localized in 1107 patients (77.4%) and generalized in 324 (22.6%). Adequate source-control and empirical antimicrobial therapy were reported in 95.2% and 88.7% of the patients. 47 isolated bacteria (6.8%) were resistant. Two (4.2%) were health-care-associated infections and 45 (95.7%) were community-acquired infections. Univariate analysis showed factor associated to resistant bacteria was the inadequacy of the empiric antimicrobial therapy (p = 0.013); at multivariated analysis factors associated with mortality were age>70 years (p = 0.003) and severe sepsis at the admission (p = 0.02); factors associated to ICU admission were: severe sepsis (p < 0.0001), generalized peritonitis (p < 0.0001), malignancy (p < 0.0001) and cardiovascular disease (p < 0.0001). Conclusion: The evolution of antimicrobial resistance, in common community-acquired infections, combined with lack of new antibiotics development are strictly linked to clinical outcomes. Adequate empirical antimicrobial therapy is fundamental to counteract bacterial resistance. Highlights: 95.7% of isolated resistant bacteria were community-acquired. Antimicrobial resistance, in common community-acquired infections, are strictly linked to clinical outcomes. Adequate empirical antimicrobial therapy is fundamental to counteract bacterial resistance.